2023
DOI: 10.1111/bjet.13392
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on reading in high‐immersion virtual reality

Regina Kaplan‐Rakowski,
Alice Gruber

Abstract: High‐immersion virtual reality (VR) is an increasingly valued environment for language learners. Although reading constitutes a core language skill, practicing reading in VR has received little attention. In this between‐subject, quantitative study, 79 intermediate learners of English at a German university were randomly assigned to view an interactive, multimedia‐rich story under two conditions. In the experimental condition, subjects (the VR group) experienced the story using a high‐immersion VR headset. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…You don't normally get to see it moving like that, being able to spin around in the app and giving you a different perspective was really cool." This increased presence aligns with research in formal learning environments, where the use of VR has been shown to improve enjoyment and engagement (Kaplan-Rakowski & Gruber, 2023;Makransky et al, 2019;Ye & Kaplan-Rakowski, 2024).…”
Section: Noticing and Observationsupporting
confidence: 74%
See 4 more Smart Citations
“…You don't normally get to see it moving like that, being able to spin around in the app and giving you a different perspective was really cool." This increased presence aligns with research in formal learning environments, where the use of VR has been shown to improve enjoyment and engagement (Kaplan-Rakowski & Gruber, 2023;Makransky et al, 2019;Ye & Kaplan-Rakowski, 2024).…”
Section: Noticing and Observationsupporting
confidence: 74%
“…VR has been seen to support learning (e.g., Dhimolea et al, 2022;Ferdig et al, 2018;Kaplan-Rakowski & Gruber, 2023;Radianti et al, 2020), which has strengthened an interest in exploring VR applications for educational purposes. The market value of VR is expected to increase threefold by 2028 (Grand View Research, 2021).…”
Section: Virtual Reality and Educationmentioning
confidence: 99%
See 3 more Smart Citations